1986
DOI: 10.1172/jci112536
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic guanosine monophosphate as a mediator of vasodilation.

Abstract: Although cyclic guanosine monophosphate (GMP)' was first described in biological samples more than two decades ago, its role in some physiological processes has only become apparent in the past few years (see references [1][2][3][4]. This relatively slow development is probably attributable to the low concentrations of the nucleotide in tissues, the complex and insensitive methods available during the early studies, and the biases many investigators had regarding its possible functions. The latter was undoubte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
341
1
11

Year Published

1988
1988
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 765 publications
(363 citation statements)
references
References 46 publications
10
341
1
11
Order By: Relevance
“…It is generally accepted that cGMP mediates vascular smooth muscle relaxation evoked by CY-ANP [14]. cu-ANP has specific receptors on cultured rat VSMC and is known to stimulate intracellular guanylate cyclase [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that cGMP mediates vascular smooth muscle relaxation evoked by CY-ANP [14]. cu-ANP has specific receptors on cultured rat VSMC and is known to stimulate intracellular guanylate cyclase [9].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this considerable binding to cells, analog III did not stimulate cGMP production in VSMC even at 10m5 M, while cu-ANP exhibited remarkable stimulation with an EDso value of 3 x lo-* M ( fig.3). These results suggest that analog III is either a competitive antagonist of cu-ANP or a socalled clearance receptor (C-receptor) agonist, which is able to bind to the C-receptor but not to the bioactive receptor (B-receptor), only the Breceptor being coupled to guanylate cyclase [14,15]. We therefore examined analog III with special reference to its effect on the a-ANPinduced production of intracellular cGMP in VSMC.…”
Section: Discussionmentioning
confidence: 99%
“…The biological importance of this ubiquitous intra-and intercellular signalling molecule was first described in the early 1980s as being part of the endothelial derived relaxing factors (Furchgott & Zawadzki 1980). NO was named "Molecule of the Year" in 1992 by the journal Science and, later that decade, studies were conducted to demonstrate its cardinal mechaits cardinal mechanism of action on vascular smooth muscle cells (Murad 1986). These studies made it clear that generation of NO by endothelial cells causes smooth muscle relaxation through activation of guanylate cyclase by nitrosation of its heme group.…”
mentioning
confidence: 99%
“…Further studies revealed that NO is released from the vascular endothelium when L-argenine is converted to L-citruline and that the reaction is facilitated by the enzyme NO synthase (NOS). [2][3][4] Nitric oxide contributes to the relaxation of smooth muscle via the following mechanism. The stimulation of NOS activity increases the release of NO, which then diffuses in to the adjacent smooth muscle cell and binds to the heme moiety of cytosolic guanylate cyclase.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of guanylate cyclase increases the intracellular concentration of cyclic guanosine monophosphate, resulting in relaxation of the smooth muscle. 4 Once released, NO is quickly inactivated by combining with hemoglobin to produce methemoglobin and eventually forming inorganic nitrate and nitrites 5 ( Figure 1). …”
Section: Introductionmentioning
confidence: 99%